UPAYA PENCEGAHAN TERJADINYA TINDAK PIDANA KEKERASAN TERHADAP WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS II BETENG AMBARAWA - Agus Hardiyanto, R.B Sularto, Purwoto (Diponegoro Law Journal, 2013)
One of the technical unit which function is take care the criminal called prison. During the punishment period, sometimes the criminals have inhumanity treatment, although there are lot of regulations related to the defendant treatment. The main problems in this paper are explain factors which cause the violation among the capcriminals themselves in Beteng Jail Ambarawa city, and also reveal the solution to avoid  the chaos in this II class jail.The type of this research of law writing using yuridis research, sources of data in this study using primary and secondary data sources. Data collection methods in this research using the writer use both observation method and interview method, then the writer analyze the result qualitively. Factors causes violation among the criminals themselves in Beteng Jail, Ambarawa city are over capasity, the comparation between the official amount and the criminals is not equal, the official understanding to their duty and also to the human right values is different. the criminals have strong willingness to escape and the monotonic situation and condition which persist for a long time. In order to solve the problems, the second class jail in Beteng Ambarawa are: develop the criminals’s personality, giving several kinds permission leave to the criminals, giving parole with certain condition and increasing surveillance.